Calcareous algae from Upper Albian - Cenomanian strata of the Potiguar basin (NE Brazil) - Granier, Bruno; Dias-Brito, Dimas [UNESP]; Bucur, Ioan I. (My University, 2008)
Calcareous Albian-Cenomanian strata in the Potiguar basin yield a number of microfossils, among which are calcareous algae (Dasycladales and Corallinales). This data, together with an inventory of previous discoveries, enabled the discussion of their biogeography. These benthic organisms probably came from the early Central Atlantic Ocean through its northwestern neck between Africa and South America and thus reached the early South Atlantic platforms.
Keywords: Albian; Biogeography; Brasil; Calcareous algae; Cenomanian; Potiguar Basin; benthos; biogeography; calcareous alga; geographical distribution; microfossil; Africa; Atlantic Ocean; Atlantic Ocean (Central); Brazil; Rio Grande do Norte; South America; algae; Corallinales; Dasycladales